2013
DOI: 10.1016/j.jceh.2013.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis E and Acute-on-Chronic Liver Failure

Abstract: Hepatitis E virus (HEV) is the most common cause of acute viral hepatitis (AVH) globally. It causes large scale epidemics of AVH across the low-and middle income countries in Asia and Africa, and also causes sporadic cases of AVH in the same geographical region. AVH due to HEV is usually an acute, self-limiting illness, similar in clinical presentation to AVH caused by hepatitis A virus (HAV). When HEV causes AVH in patients of chronic liver disease it may worsen rapidly to a syndrome called acute-on-chronic l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
75
2
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(84 citation statements)
references
References 43 publications
3
75
2
2
Order By: Relevance
“…to 75%) with a median short-term mortality rate of 34% (range: 0%-100%). 58 One study from India reported a 70% 12-month mortality rate in patients with HEV infection superimposed upon chronic liver disease and interestingly, HEV infection was associated with a higher mortality rate than decompensation due to any other cause. 64 However, a study from South-East England suggested that there are 80 000-100 000 infections per year in England, the majority of which are asymptomatic.…”
Section: Genotypementioning
confidence: 99%
“…to 75%) with a median short-term mortality rate of 34% (range: 0%-100%). 58 One study from India reported a 70% 12-month mortality rate in patients with HEV infection superimposed upon chronic liver disease and interestingly, HEV infection was associated with a higher mortality rate than decompensation due to any other cause. 64 However, a study from South-East England suggested that there are 80 000-100 000 infections per year in England, the majority of which are asymptomatic.…”
Section: Genotypementioning
confidence: 99%
“…It is important to note that this is not always easy to discern. In the Asian subcontinent, HBV reactivation is a significant precipitant of ACLF, while superimposed HEV is a major cause of ACLF in India [39][40] . As well as viral infection, bacterial and fungal infections may also result in bacterial translocation and therefore contribute toward the development of the SIRS.…”
Section: Insult/injurymentioning
confidence: 99%
“…HEV infection is attributable not only as a common cause of acute liver failure in India but also to worsening liver function in patients with underlying chronic liver disease, an entity termed as acute-on-chronic liver failure (ACLF)34. During an epidemic, women in the late trimester of pregnancy are infected more frequently (12-20%) than non-pregnant women and men (2-4%)35.…”
Section: Hepatitis E Virus (Hev)mentioning
confidence: 99%